The Impact of Artificial Intelligence on Graphic Design - Durusoy, Okan (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The integration of artificial intelligence (AI) and machine learning in creative industries has deeply revolutionized traditional processes of artistic production and design. Of these, the design industry, and graphic design in specific, has been the fastest to evolve due to the appearance of new generative AI tools for generating, editing, and analysing visual content with very low input from a human. As news of these advancements broke, designers were both interested and anxious about the future, questioning the role of the designer, the importance of human creativity and the potential lasting effects of the releases on the industry. This paper performs a thorough literature review on diverse dimensions of the influence of AI technologies in graphic design in terms of how AI technologies affect design processes, industry landscapes, and professional identity of graphic designers. Both the positive and negative impact of the integration of AI is critically studied, and the study is based on recent academic and industry views. According to these findings, the study provides a set of prescriptions to promote the responsible and effective use of AI within the graphic design industry.